PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. AUTO NUSA ABADI KUPANG - Christin Anggy Venny Saba; Tarsusius Timuneno; Merlyn Kurniawati (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This study entitled "The Effect of Compensation, and Work Environment on employee performance in CV. Auto Nusa Abadi ". The purpose of this study was to determine the the effect of compensation and work environment on employee performance at CV. Auto Nusa Abadi. The approach used by researchers is a quantitative approach. The sample contained in the study were 33 respondents. The analysis technique used is the instrument test, classic assumption test, multiple regression test, coefficient of determination test, t test and f test. The results of the coefficient of determination test show that the Adjusted R Square coefficient of 0.811 means that after conducting research, it is known that 81.11% compensation and work environment affect employee performance, while the remaining 18.89% is influenced by other variables not explained in this research. The test results partially compensation and work environment variables have a significant effect on employee performance. Simultaneous test results of compensation and work environment variables influence the decision to become a customer at CV. Auto Nusa Abadi. Keyword: Compensation, Work Environment, performance